Legal and Criminal Confrontation of Usurious Transactions (Al-Mukhtar Journal of Legal Science, 2024)
This study deals with the confrontation methods of Islamic Sharia and criminal law of usurious transactions, which have increased significantly and are noticeable in recent times, and the reason is due to the financial liquidity crisis resulting from the collapse of the political power and economic structure of the Libyan state, so that people are forced to borrow regardless of the value of the interest imposed on them.  Be that as it may, the research needed to deal with this question in both its religious and legal aspects, in order to show the characteristics of the approach of each of them to limit or prevent usurious transactions. How has Islamic Sharia dealt with this issue, and what is its approach to it, and how has our punitive law dealt with it, and does it agree with Sharia rulings in this regard? And we concluded that the Libyan legislature did not criminalize all forms of usurious transactions, but rather limited them to some of them. It has also failed to follow up on the criminalization of the new forms of these and the usurious tricks that have appeared, the purpose of which is to show the transaction in a legitimate form, which is the opposite.
Keywords: Usurious Transactions; Punishment; Sharia; Zakat